Fixed Point Theorems for Generalized Mizoguchi-Takahashi Graphic Contractions - Nawab Hussain; Jamshaid Ahmad; Marwan Amin Kutbi (Journal of Function Spaces)
Remarkable feature of contractions is associated with the concept Mizoguchi-Takahashi function. For the purpose of extension and modification of classical ideas related with Mizoguchi-Takahashi contraction, we define generalized Mizoguchi-Takahashi G-contractions and establish some generalized fixed point theorems regarding these contractions in this paper. Some applications to the construction of a fixed point of multivalued mappings in ε-chainable metric space are also discussed.